2019
DOI: 10.1155/2019/3094154
|View full text |Cite
|
Sign up to set email alerts
|

Prx1-Expressing Progenitor Primary Cilia Mediate Bone Formation in response to Mechanical Loading in Mice

Abstract: Increases in mechanical loading can enhance the addition of new bone, altering geometry and density such that bones better withstand higher forces. Bone-forming osteoblasts have long been thought to originate from progenitors, but the exact source is yet to be identified. Previous studies indicate osteogenic precursors arise from Prx1-expressing progenitors during embryonic development and adult fracture repair. However, it is unknown whether this cell population is also a source for mechanically induced activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…This diminished mechanoadaptive response is in agreement with work examining a global knockout of AC6 , where AC6 deletion resulted in an inhibited response to ulna loading, ( 29 ) and further strengthens the potential involvement of the primary cilium, to which AC6 localizes, in bone mechanoadaptation. ( 41,42 ) Furthermore, as with the Lepr‐cre;tdTomato mouse, no change was found in the percentage of Lepr‐cre;tdTomato + cells on the bone surface or embedded within the bone. The lack of bone formation and the failure of loading to induce migration of LepR + cells from the marrow to the bone surface in Lepr‐cre;tdTomato;AC6 fl/fl mice are consistent with our hypothesis that loading‐induced bone formation occurs via Lepr‐cre;tdTomato + cells, and that this process requires AC6.…”
Section: Discussionmentioning
confidence: 95%
“…This diminished mechanoadaptive response is in agreement with work examining a global knockout of AC6 , where AC6 deletion resulted in an inhibited response to ulna loading, ( 29 ) and further strengthens the potential involvement of the primary cilium, to which AC6 localizes, in bone mechanoadaptation. ( 41,42 ) Furthermore, as with the Lepr‐cre;tdTomato mouse, no change was found in the percentage of Lepr‐cre;tdTomato + cells on the bone surface or embedded within the bone. The lack of bone formation and the failure of loading to induce migration of LepR + cells from the marrow to the bone surface in Lepr‐cre;tdTomato;AC6 fl/fl mice are consistent with our hypothesis that loading‐induced bone formation occurs via Lepr‐cre;tdTomato + cells, and that this process requires AC6.…”
Section: Discussionmentioning
confidence: 95%
“…The source of osteoblast progenitors in vivo is still under debate. They can be found in bone marrow (MSCs accounting for 0.001 to 0.01 % nucleated cells) and periosteum [ 20 , 21 ]. Recently, new osteoprogenitors called transcortical perivascular cells (2–3% of Lin − cells from the digested cortical bone fraction) were identified [ 22 ].…”
Section: Osteoblast/osteoclast Balance In Bone Remodeling and Repamentioning
confidence: 99%
“…To investigate the degree of Prx1 + MSC participating in bone regeneration in young and aged mice, 4 weeks and 12 months old Prx1CreER-GFP;Rosa26 tdTomato mice (n = 3 per group) were received intraperitoneal injections of 75 mg/kg bodyweight tamoxifen (Sigma-Aldrich) for 5 days before closed left femoral bone fracture was made. 20 At 2 weeks after surgery, the mice were killed, and the femurs were harvested for immunofluorescence.…”
Section: Lineage Tracing Analysismentioning
confidence: 99%
“…18 These Prx1 positive cells (Prx1 + MSCs) have the potential of osteogenic and chondrogenic differentiation and are essential for limb development and bone regeneration. [18][19][20] Duchamp de Lageneste et al found that Prx1 + MSCs can efficiently contribute to cartilage and bone regeneration, while periostin was essential for maintaining the Prx1 + MSCs pool. 21 Therefore, we wondered that if the quantity of Prx1 + MSCs would decrease with age and affect bone regeneration ability in aged mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation